2017
DOI: 10.1080/16549716.2017.1387985
|View full text |Cite
|
Sign up to set email alerts
|

Retention and use of newborn resuscitation skills following a series of helping babies breathe trainings for midwives in rural Ghana

Abstract: Background: The Helping Babies Breathe (HBB) program teaches basic newborn resuscitation techniques to birth attendants in low-resource settings. Previous studies have demonstrated a decrease in mortality following training, mostly in large hospitals. However, low-volume clinics in rural regions with no physician immediately available likely experience a greater relative burden of newborn mortality. This study aimed to determine the impact of HBB trainings provided to rural Ghanaian midwives on their skills re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 17 publications
4
44
2
Order By: Relevance
“…It is clear that knowledgeable care providers can apply their knowledge to skill. Paradoxically, receiving NR refresher training was not associated with the multivariate logistic analysis of this study, but in many studies, NR training was found to be significantly associated with retention of NR skill [23,30,[50][51][52][53][54][55].…”
Section: Plos Onecontrasting
confidence: 66%
“…It is clear that knowledgeable care providers can apply their knowledge to skill. Paradoxically, receiving NR refresher training was not associated with the multivariate logistic analysis of this study, but in many studies, NR training was found to be significantly associated with retention of NR skill [23,30,[50][51][52][53][54][55].…”
Section: Plos Onecontrasting
confidence: 66%
“…The HBB refresher training involved all the staff responsible for attending births/resuscitations, reinforcing the existing frequent brief training programme, which we have shown to be associated with a reduction in mortality 12. This addresses the concern raised by Makene et al and Eblovi et al on the necessity for on-job practice and strengthening of supportive supervision to ensure quality in resuscitation 34 35…”
Section: Discussionmentioning
confidence: 74%
“… 15 , 24 , 34 36 However, published reports also mentioned the deterioration of skills after HBB workshops, which mirrored the experiences of other resuscitation training programs. 24 , 37 , 38 For the effective performance of these lifesaving skills to impact neonatal mortality and stillbirth rates, providers need to be able to perform basic resuscitation and bag-mask ventilation, if needed, within “The Golden Minute” after birth.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of ongoing practice, even when studied in rural providers—such as village midwives and birth attendants—1 year after their initial HBB training, showed retention of basic resuscitation skills with ongoing practice and/or refresher trainings and reductions in fresh stillbirth and early neonatal mortality rates. 38 , 42 , 43 …”
Section: Methodsmentioning
confidence: 99%